Optimal Pressure Vessel Project Schedule Planning with Critical Path Method (CPM) at PT. XYZ - Yustina Ngatilah; Caecilia Pujiastuti; Isna Nugraha; Dwi Qomariah Arifin (Nusantara Science and Technology Proceedings)
Project scheduling is one element of planning that provides various information for time efficiency to complete a project. The success of a project starts from the planning and preparation of the correct and systematic stages. Every company must try to complete the work on time as scheduled to avoid various losses that arise. This research aims to determine the activities that are classified as critical in the production of pressure vessels belonging to one of the leading companies in Indonesia engaged in natural gas processing, which PT is carrying out. XYZ. This study also compares the costs incurred to complete the pressure vessel project with a normal and accelerated duration of work. The method used is the Critical Path Method (CPM) and Microsoft Project software. CPM is a network analysis that aims to optimize the total project cost by reducing completion time. The use of the CPM method can save time in completing various stages of a project. The initial project duration is 952 working hours or 119 working days. It can be accelerated to 884 working hours or 111.25 working days, 7.75 days faster than the initial schedule. There are 24 critical activities, and the labor cost that must be spent is IDR 72,034,400.00 under normal conditions, while the labor cost that must be spent for the acceleration condition is IDR 76,626,400.00.